1. ReKOMendacje Postępowania w ostrych zakażeniach dróg oddechowych u dzieci w czasie pandemii SARS-CoV-2 dla lekarzy Podstawowej Opieki Zdrowotnej – KOMPAS COVID - Kuchar, Ernest; Karlikowska-Skwarnik, Monika; Szenborn, Leszek; Jackowska, Teresa; Doniec, Zbigniew; Mastalerz-Migas, Agnieszka (Family Medicine & Primary Care Review, 2021)
Respiratory tract infections are one of the most common health problems among children during the winter season. Viruses are responsible for a vast majority of respiratory tract infections. Bacterial infections usually affect specific locations (for example, otitis media, nasal sinuses, lungs or, sometimes, throat) and are more frequent in risk groups, or they can complicate a previous viral infection. During the ongoing COVID-19 pandemic, it is essential to consider SARS-CoV-2 as a possible causative agent for any infectious disease affecting the respiratory tract. Recommendations aim to establish an optimal manner for management of respiratory infections. Any patient should be pre-screened by telephone consultation to reduce the risk to healthcare workers. Regardless of the infection's etiology and location, the top priority should be to determine the patient's general condition and the place of treatment and treatment method (hospital, home, symptomatic, antimicrobial). For epidemic reasons, it is advisable to exclude infection with the new coronavirus in the case of a doubtful clinical picture, as well as patients with SARS-CoV-2 infection. The primary purpose of any consultation is to choose the best treatment for the patient (ambulatory/hospital/symptomatic/antimicrobial), and it is not always crucial to know the exact etiology of the infection. Due to epidemiologic reasons, it is reasonable to exclude SARS-CoV-2 infection in every patient with atypical symptoms or after contact with a person infected with SARS-CoV-2.